KONTRIBUSI USAHATANI CENGKEH TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA RAANAN BARU 2, KECAMATAN MOTOLING BARAT - Gogen Klif N. Kumaat; Theodora M. Katiandagho; Mex L. Sondakh (AGRI-SOSIOEKONOMI, 2015)
This study aims to find out how much farm income clove and clove farming contribution to total household income of farmers in the New Raanan 2 Village. The study was conducted from March to June 2015. Samples size was 30 respondents using purposive sampling method. Results from this study indicate clove farm income is a source of income which contributes most of all sources of income of farming families. However, in terms of farm income cloves there are several indicators that show the need for increased production and expenditure savings, given harvest once a year and selling prices are volatile. Farmers need to maintain the indicators that have been rated excellent for this, such as vacant devote time to other farms and use clove farm income to education, such as sending children to school.